2006
DOI: 10.1001/archotol.132.10.1041
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Development of Hypothyroidism and Improved Survival in Patients With Head and Neck Cancer

Abstract: To determine if the development of hypothyroidism has an effect on the outcome of advancedstage head and neck squamous cell carcinoma. Design: Retrospective database analysis. Setting: Tertiary care center. Patients: The study population comprised 155 patients with advanced-stage head and neck squamous cell carcinoma. Interventions: Patients underwent radiation therapy alone or in combination with chemotherapy and surgery when indicated. Main Outcome Measures: Kaplan-Meier analysis was used to assess survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 17 publications
2
42
1
2
Order By: Relevance
“…It has been suggested that the thyroid hormone, through stimulation of other growth factors, may represent a growth-stimulating signal in several tumor types (Trentin et al 2001). Thyroid hormones may be permissive for tumor growth and may reduce survival in recurrent brain tumors (Hercbergs et al 2003) and in head and neck cancer (Nelson et al 2006). Moreover, a relationship between hypothyroidism and reduced incidence and less aggressiveness of breast cancer was demonstrated (Cristofanilli et al 2005).…”
Section: Hypothyroidism and Tumor's Outcomementioning
confidence: 99%
“…It has been suggested that the thyroid hormone, through stimulation of other growth factors, may represent a growth-stimulating signal in several tumor types (Trentin et al 2001). Thyroid hormones may be permissive for tumor growth and may reduce survival in recurrent brain tumors (Hercbergs et al 2003) and in head and neck cancer (Nelson et al 2006). Moreover, a relationship between hypothyroidism and reduced incidence and less aggressiveness of breast cancer was demonstrated (Cristofanilli et al 2005).…”
Section: Hypothyroidism and Tumor's Outcomementioning
confidence: 99%
“…It has therefore been suggested that thyroid function might influence cancer development (1). According to this hypothesis, thyroid hormones could stimulate tumor growth (2,3) and thus be associated with increased risk, whereas hypothyroid function could lead to a reduced risk and a more favorable prognosis in patients with cancer (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the prognosis of patients with cancer, patients with head and neck cancer who develop hypothyroidism may experience longer survival (3). In patients with breast cancer, it has been suggested that the presence of thyroid peroxidase antibodies, indicating autoimmune thyroid disease, may be associated with improved survival (9).…”
Section: Introductionmentioning
confidence: 99%
“…подобном клиническом наблюдении 15 он-кологических больных, получающих иммунотера-пию ИЛ-2 и LAK (lymphokine-activated killer cells), у 5 из 7 пациентов с индуцированным гипотирео-зом была достигнута полная (n = 1) или частичная (n = 4) ремиссия [36]. Ретроспективный анализ, выполненный Nelson et al (2006) на 155 больных первичным плоскоклеточным раком головы и шеи, диагностированным в период с 1989 по 1997 гг (Кливленд, Огайо, США), продемонстрировал, что тиреоидный статус коррелирует с исходами ле-чения. Так, у 75 пациентов с индуцированным в ре-зультате воздействия цитостатиков или имеющимся до начала терапии лабораторно подтвержденным гипотиреозом зарегистрирована более длительная продолжительность безрецидивного периода и до-стигнута более высокая выживаемость, а также бо-лее низкий риск развития рецидива (ОР 0,49; 95 % ДИ 0,28-0,88, p = 0,02) и смерти от злокачественно-го новообразования (ОР 0,30; 95 % ДИ 0,17-0,52, p < 0,001) [22].…”
Section: роль индуцированного гипотиреоза при специфи-ческом проивоопunclassified